Trends in certifications of overall vision impairment and that due to diabetic retinopathy/maculopathy in England and Wales, 2009/2010 to 2019/2020: a retrospective database analysis - Catey Bunce; Gwyn Samuel Williams; David Owens; Wen Xing; Rhianon Reynolds; Antra Zekite; Declan Flanagan; RL Thomas; Rebecca John (BMJ Open)
Objectives This study aims to report the trends in the certification of both sight impairment (SI) and severe sight impairment (SSI) in England and Wales during the period of 2010 to 2020, prior to the COVID-19 pandemic. The focus is on diabetic retinopathy/maculopathy as the key causative factor.Design Retrospective database analysis.Setting England and Wales.Participants Individuals certified as SI or SSI.Outcome measures Trends in certification of vision impairment in England and Wales due to any cause, with specific attention to diabetic retinopathy.Methods Certifications of vision impairment made by ophthalmologists in England and Wales were recorded and copies were sent to Moorfields Eye Hospital for epidemiological analysis. All certificates completed in England and Wales over an 11-year period, from April 2009 to March 2020, were queried and analysed on an annual basis. This analysis included all causes, and where both the main cause was diabetic eye disease or where diabetic eye disease was a contributory cause among multiple pathologies. Poisson regression was employed to analyse changes in trends over time for certifications of vision impairment.Results In England, from 2010 to 2020, there was a small but significant reduction (p<0.001) in the overall rate of certifications for SI and SSI due to any cause, from 43.4 certifications per 100 000 people to 41.7 per 100 000 people. Conversely, in Wales, an initial decline was observed, with a decrease from 50.6 to 40.1 per 100 000 people from 2009/2010 to 2014/2015, respectively. This rate subsequently increased to 51.8 per 100 000 by 2019/2020; however, this was not statistically significant (p=0.087). Individuals in Wales had a 9% higher certification rate compared with those in England (1.09 (95% CI 1.07, 1.10)). For diabetic retinopathy, certifications in England significantly decreased from 72.8 to 41.3 per 100 000 people over the study period; in Wales, the certification rate initially declined from 82.3 to 47.1 per 100 000 by 2016/2017 before increasing to 55.5 per 100 000 in 2019/2020. Despite this fluctuation, there was a significant decrease in certifications due to diabetic retinopathy in Wales during the study period.Conclusions The findings underscore the importance of understanding regional variations in certification rates, particularly in the context of diabetic retinopathy. Despite fluctuations in Wales, the overall reduction in certifications due to diabetic retinopathy in both regions suggests a critical need for ongoing public health initiatives aimed at preventing vision impairment linked to diabetes. However, to provide a true reflection of the burden of vision impairment and its various causes, ensuring that all eligible people are certified is a prerequisite. Continuing attempts to limit the incidence of vision impairment due to diabetic retinopathy remain a priority.